The making of a dangerous vector: factors shaping the vector competence of Aedes mosquitoes - Wu, Yang; Wu, Jie; Wu, Qipeng; Cai, Huiling; Hu, Jia; Lin, Zhiwei; Liao, Ruyan (Frontiers in Cellular and Infection Microbiology, 2025)
Aedes mosquitoes are among the world’s most significant arbovirus vectors, transmitting pathogens such as dengue, chikungunya, and Zika viruses. However, key species like Aedes aegypti and Aedes albopictus exhibit notable differences in their vector competence, a trait of critical epidemiological importance. Vector competence is a complex phenotype, intrinsically defined by the efficiency with which a virus can overcome key tissue barriers, primarily the midgut and salivary glands. This review synthesizes the current understanding of the multifactorial drivers behind this variation through a comparative analysis of intrinsic determinants—including the vector’s genetic background, innate immunity, co-evolution with the virus, tissue barriers, and gut microbiota—and extrinsic factors, such as climatic conditions and anthropogenic pressures. By dissecting these mechanisms, this review provides a critical reference for assessing the epidemic risks of mosquito-borne diseases and aims to inform the development of more precise, next-generation vector control strategies.